Photocured thiol-ene based optical fluorescence sensor for determination of gold(III) - KÖK YETİMOĞLU, ECE; KAHRAMAN, MEMET VEZİR; ÇUBUK, SONER (ELSEVIER SCIENCE BV, 2014)
This study describes the preparation and the characterization of a new thiol-ene based polymeric fluorescence sensor by photo initiated polymerization of trimethylolpropane tris(3-mercaptopropionate), 2-hydroxyethylacrylate, and 2,4,6-triallyloxy-1,3,5-triazine which are used as monomers and also a photo initiator (2,2-dimethoxy-2-phenylacetophenone) for its usage as optical sensor for gold ions. The thiolene based polymeric membrane sensor was characterized by using attenuated total reflectance-fourier transform infrared spectroscopy (ATR-FTIR) and scanning electron microscopy (SEM). The response characteristics of the sensors including dynamic range, pH effect, response time, and the effect of foreign ions were investigated. Fluorescence spectra showed that the excitation/emission maxima of the membrane were at 3791425 nm, respectively (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Gold(III); Fluorescence spectroscopy; Membrane; Optical sensor; Thiol-ene; Photo curing; ATOMIC-ABSORPTION-SPECTROMETRY; PRECONCENTRATION SYSTEM; ONLINE SEPARATION; MASS-SPECTROMETRY; TRACE GOLD; AU3+; CHEMOSENSORS; EXTRACTION; SAMPLES; IONS